Cellulase saccharification of rooibos biomass pretreated with horseradish peroxidase - Mohotloane, Mamosela Marriam (University of the Free State, 2023)
Worldwide industrilization has led to economic activities (such as burning of fossil fuels) that enhance greenhouse gas emmissions in the atmostphere, resulting in a phenomenon known as global warming. Therefore, the use of agricultural residues to produce second generation biofuel (2G) can lead to a reduction in carbon dioxide (CO₂) emissions. However, it has been challenging to produce biofuel from agricultural residues, due to the presence of lignin in the plant biomass. Lignin causes non-specific binding of the glycoside hydrolases (GHs) to the biomass, reducing their efficiency. Therefore, it is vital to remove lignin before the production of biofuel. Most chemical methods are effective in removing lignin but are expensive and hazardous to the environment and human health. Hence, there is a need to find cheaper alternative methods that are sustainable, renewable, and environmentally friendly, such as the use of biological pretreatment. This study aimed to delignify fermented rooibos using purified horseradish peroxidase (HRP) and to formulate a holocellulolytic enzyme cocktail for conversion of the delignified fermented rooibos biomass to soluble sugars. The results indicated that HRP was partially purified, with activity on guaiacol, 8-aminoquinoline, and decolourised methylene blue dye. HRP had a pH optimum of 4.5 and displayed a mesophilic temperature range. It had higher affinity towards guaiacol (Km= 0.082 mg/mL) compared to 8-aminoquinoline (Km= 0.221 mg/mL), but it efficiently catalysed both guaiacol (63436.48 s⁻¹ . mg/mL) and 8-aminoquinoline (59189.81 s⁻¹ . mg/mL). The partially purified HRP was used to pretreat the fermented rooibos biomass to remove lignin. Scanning electron microscopic (SEM) analysis showed lignin removal, exposed microcrystalline cellulose fibres and the changed structure of the biomass. These observations were corroborated by the Fourier Transform Infrared (FTIR) spectroscopy, which showed reduction of ester-linkages and phenolic functional groups. X-ray diffraction (XRD) analysis confirmed that pretreated biomass had reduced crystallinity compared to the control (untreated) biomass. Cellulose model substrates (Avicel and filter paper) were used to elucidate the mechanisms HRP uses to reduce the crystallinity of cellulose fibres. The results suggest that HRP treatment increased cellulose crystallite sizes from 45 to 47 nm at the 002 lattices in Avicel and decreased from 60.7 to 59.3 nm in filter paper. These modifications enhanced hydrolytic enzymes’ accessibility (demonstrated using endoglucanase) to the pretreated rooibos biomass than the control. Commercial cellulases and xylanases were used to formulate the holocellulolytic enzyme cocktail (HEC). The HEC converted the HRP delignified rooibos biomass to soluble sugars, producing about 95% yield of total reducing sugars at enzymes load of 25 mg /g biomass.
Dissertation (M.Sc.(Botany))--University of the Free State, 2023
Keywords: Biomass energy; Rooibos; Horseradish peroxidase; Holocellulolytic enzyme cocktail